Fabrication and characterization of Schottky barrier diodes on rutile TiO2 - Julie Bonkerud; Christian Zimmermann; Philip Michael Weiser; Thomas Aarholt; Espen Førdestrøm Verhoeven; Lasse Vines; Eduard V Monakhov; Frank Herklotz (Materials Research Express, 2020)
Schottky barrier diodes (SBDs) were fabricated by depositing Pd, Pt or Ni on single crystal, conductive n -type rutile TiO _2 using e-beam evaporation. As-grown and nominally undoped rutile TiO _2 single crystals are semi-insulating, and were heat-treated in forming gas flow, N _2 flow or H _2 gas to obtain conductive n -type crystals displaying electrical conductivities in the range of $(0.5-8)× {10}^{-2}\,{{\rm{Ω }}}^{-1}\,{cm}^{-1}$ . Additionally, SBDs were deposited on Nb-doped conductive n -type rutile TiO _2 with a conductivity of around $0.25\,{{\rm{Ω }}}^{-1}\,{cm}^{-1}$ . Generally, SBDs displaying a rectification of up to eight orders of magnitude were obtained, when comparing the current under reverse and forward bias. The extracted ideality factors were in the range of $1.1-4.0$ . From Capacitance-Voltage measurements, the built-in voltage was derived to be around $1.2\,{\rm{V}}--1.9\,{\rm{V}}$ , depending on the doping concentration of the specific TiO _2 single crystal. Series resistances as low as $19\,{\rm{Ω }}$ were achieved. A considerable variation in the electrical characteristics of different SBDs deposited on the same crystal was found, regardless of the metal or doping strategy used. Moreover, the SBD characteristics change over time, particularly seen as a degradation in rectification, mainly related to an increase in the current under reverse bias. Additional surface treatments such as boiling in H _2 O _2 and etching in HF do not have a significant effect on the quality of the SBDs. Clear indications for poor adhesion between TiO _2 and Pd are shown. In conclusion, we demonstrate the fabrication of SBDs which are suitable for studying the fundamental properties of metal/TiO _2 junctions and the characteristics of electrically-active defects in TiO _2 using space-charge spectroscopy.